Analisis Pengendalian Kualitas Produksi Sperpart Kendaraan Roda Empat Dengan Metode Statistical Quality Control (SQC) di PT Adyawinsa Stamping Industries - Muhammad Khoiri Muslim; Ayudyah Eka Apsari (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2024)
The development of the automotive world is currently growing rapidly, in achieving the company's goals to produce the quality of products that are in accordance with the customer's expectations. Companies must be able to create products with good quality, so that companies are able to compete in the market and can develop their business. There are many methods that discuss quality with their own characteristics. This study aims to analyze the implementation of production quality spare production of four-wheeled vehicles, especially the component number 5761 at PT Adyawinsa Stamping Industrials. The method applied in this study was the Statistical Quality Control (SQC) method. A quality control analysis was carried out using ventral statistical tools in the form of checking sheet, histogram, control chart, pareto chart, causal diagrams due to, recording the diagram, and stratification. The results of this study indicate that the product quality at PT Adyawinsa Stamping Industriales is still found in product disability. Main factors that influence product disability include due to human factors, machines, methods, materials, and environment.